Changes in Obstetrical Practices and Pregnancy Outcomes Following the ARRIVE Trial. Issue 1 (22nd March 2023) - Gilroy, L.C.; Al-Kouatly, H.B.; Minkoff, H.L.; McLaren, R.A.
Abstract : ( Am J Obstet Gynecol . 2022;226:716.e1–716.e12) As cesarean delivery rates approach an all-time high in the United States and other developed countries, mothers and neonates are at increased risk for morbidities associated with this mode of birth. Data from the 2018 ARRIVE (A Randomized Trial of Induction Versus Expectant Management) trial showed a decrease in cesarean delivery rates and hypertensive disorders when obstetric practices shifted to prioritize induction for 39-week, low-risk, singleton, nulliparous births. Further, meta-analysis demonstrated 39-week inductions lower the risk of infection in the peripartum period, result in fewer NICU (neonatal intensive care unit) admissions and lessen perinatal mortality. As there is a well acknowledged "evidence-to-practice" gap it is not well understood if there has been wide-spread clinical uptake of the recommendation for obstetricians to offer induction to low-risk nulliparous women at 39 weeks. The question of broad change in obstetrical practice and perinatal outcomes following the ARRIVE trial is investigated.